Assessment of heavy metal sources and health risks in soil-crop systems of fragmented farmland - Lei Tong; Aoran Yang; Mingyue Fan; Daikun Zheng; Ji Li; Hanlin Liu; Chenggen Li; Yongqiong Tang; Longfeng Cheng (Frontiers in Public Health, 2025)
Heavy metal contamination in agricultural ecosystems poses significant risks to human health. Metals accumulating in soil-crop systems can be absorbed and concentrated by crops. Chronic exposure through the consumption of contaminated crops may lead to severe health consequences. This study investigated eight common heavy metals (Cd, Ni, As, Cu, Hg, Pb, Cr, Zn) in the soil-crop system of Wanzhou District, Chongqing City, and performed a probabilistic risk analysis using Monte Carlo simulation. The study results show that for non-carcinogenic risks, the total hazard quotient for adults (2.365) and children (1.176) both exceed the safety threshold of 1.0, with As contributing significantly to population health risk. For carcinogenic risks, the total carcinogenic risk for adults (2.28 × 10−3) and children (1.11 × 10−3) significantly surpass the unacceptable risk level of 1.0 × 10−4, with As, Cr, Cd, and Ni presenting particularly high carcinogenic risks to the population. Additionally, the sensitivity analysis revealed that the concentration (C) of heavy metals in crops is a key exposure parameter influencing the health risks for both adults and children. Given the significant contributions of As, Cr, Cd, and Ni to health risks, these metals should be prioritized for monitoring and control. Long-term intake of crops with excessive heavy metal content increases health risks, highlighting the urgent need to address heavy metal pollution in urban fragmented farmland soil-crop systems.